Pengelolaan Zakat Di Lazis Jateng Ditinjau Dari Undang-Undang Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat(Studi di Lazis Jateng Cabang Kota Surakarta) - Arradea, Bill Ifqi; , Mutimatun Ni'ami, S.H., M.Hum (2016)
Zakat is one of the Five Pillars of Islam, which is a religious obligation for all Muslims who meet the necessary criteria of wealth.and allocated for those who deserve it. In the hand of proper management, Zakat is a source of potential funds that can be used to reach the general welfare of the whole society. Therefore, to optimize the practice of zakat, government made Badan Amil Zakat (BAZ) and Lembaga Amil Zakat (LAZ), which are responsible for managing and distributing zakat fund to people who deserve it, so that people can easily fulfill their obligations to pay the zakat, and for the sake of society welfare goal. With the development of the funds zakat effective and innovative as well as productive then it can help resolve the problem of proverty happended in Indonesia in general and in the city surakarta in particular. So it is expected to change the condition of a mustahik into a muzakki, as well as can be created people's welfare. Keyword: Zakat, Zakat Management, Lazis.